Ontogenetic Changes and Environmental Hypoxia: Responses of Two Fish Species to Low Oxygen Concentrations at Early Life Stages - Balfour, David Leigh (Virginia Tech, 1999)
Hypoxia refers to any condition in which the water is less than fully saturated with oxygen. Although it is generally accepted that adults are more tolerant of hypoxic conditions than larval stages, there is little information to support this assumption. To determine whether reduced concentrations of dissolved oxygen (DO) affect fishes differently during various early life stages, I examined the responses of two species of fish (fathead minnows (Pimephales promelas) and rainbow trout (Oncorhynchus mykiss)) exposed to low dissolved oxygen concentrations at different ages during the first 100 days post-hatch. The changes in oxygen requirements and respiratory patterns that occur during ontogeny and exposure to hypoxia were observed. The results of this study suggest that the early larval stages appear to be at least as tolerant of short-term exposure to low dissolved oxygen concentrations as the older, more developed stages. Fathead minnows underwent a gradual transition from being metabolic conformers to regulators during development. Hemoglobin appeared to be playing a larger role in oxygen supply in the early post-hatch trout than in the minnows. Fathead minnow larvae produced relatively low concentrations of lactate upon exposure to hypoxia. Conversely, rainbow trout larvae exhibited significant increases in lactate concentration under similar conditions. This implies that there is a threshold oxygen concentration below which trout larvae utilize anaerobic metabolism to provide additional energy. Lactate dehydrogenase activity increased as the rainbow trout larvae aged, suggesting that they develop an anaerobic capacity which could be used to provide additional energy during hypoxia. The minnows did not exhibit this increase in activity. The ability of larval fishes to detect and avoid hypoxic conditions was also examined. The overall trends suggest that throughout this period of development, both fish species gradually leave an area as the dissolved oxygen concentration decline. Both species appeared to leave ...